Infant Early Gut Colonization by Lachnospiraceae: High Frequency of Ruminococcus gnavus - Sagheddu, Valeria; Patrone, Vania; Miragoli, Francesco; Puglisi, Edoardo; Morelli, Lorenzo (Frontiers in Pediatrics, 2016)
Lachnospiraceae is a bacterial family usually isolated from human and mammalian intestinal microbiota. However, its presence and role in the infant microbiota is not fully elucidated. This may due to the strictly anaerobic behavior of its members that hampers the possibility of culture-dependent enumeration. Here, we report on the presence of this bacterial group, using biomolecular techniques, in stool samples from 25 babies aged between one and 24 months. Denaturing gradient gel electrophoresis (DGGE) was used as a first detection step and data were confirmed by quantitative PCR (qPCR). The DGGE showed the presence of Lachnospiraceae in infant fecal specimens and indicated the prevalence of Ruminococcus gnavus (R. gnavus). The qPCR confirmed the presence of the Clostridium XVIa group, Blautia genus, and R. gnavus, which are the main members of this family. We detected R. gnavus in 22 of 25 (88%) samples with a qPCR probe assay. Despite the difficulties associated with their detection and enumeration, Lachnospiraceae, and in particular R. gnavus, should be included in future studies on the infant microbiota composition.